Virtual platforms in meaningful learning in students of private universities in Lima during the Covid 19 pandemic - Raggio Ramirez, Giuliana del Socorro (2022)
In the educational context, the health emergency caused by the Covid-19 pandemic led to changes in teaching, technology and administration, one of the most common pedagogical adjustments being the use of virtual platforms for teaching, mainly in universityeducation. That is why the objective of this study is to determine the influence of the virtual platform Classroom and its dimensions (informative, practical , communicative and tutorial and evaluative) in the meaningful learning of students from private universities in Lima, Peru. The research presents a quantitative, empirical-analytical and positivist approach, of a basic type and non-experimental design. The sample consisted of 100 students from different careers at private universities in Lima-Peru, to whom two questionnaires were applied on a Likert scale, validated by expert judgment, with a Cronbach's Alpha of 0.910 and applied through the questionnaire form. Google. According to the results obtained, it is concluded that virtual platforms and theirdimensions have a positive impact on meaningful learning in students of private universities in Lima, Peru. The results obtained present an updated and reliable base that can be used to evaluate the incidence of virtual platforms in student learning, in addition, the implications are discussed and recommendations for further studies and practices are provided.